Divide and Correct: Using Clusters to Grade Short Answers at Scale - Brooks, Michael; Basu, Sumit; Vanderwende, Lucy; Jacobs, Chuck (ACL - Association for Computational Linguistics, 2014)
In comparison to multiple choice or other recognition-oriented forms of assessment, short answer questions have been shown to offer greater value for both students and teachers; for students they can improve retention of knowledge, while for teachers they provide more insight into student understanding. Unfortunately, the same open-ended nature which makes them so valuable also makes them more difficult to grade at scale. To address this, we propose a cluster-based interface that allows teachers to read, grade, and provide feedback on large groups of answers at once. We evaluated this interface against an unclustered baseline in a within-subjects study with 25 teachers, and found that the clustered interface allows teachers to grade substantially faster, to give more feedback to students, and to develop a high-level view of students’ understanding and misconceptions.